Phytochemical Screening of Secondary Metabolites, Antioxidant and Antibacterial Activities of Kalangkala Plant (Litsea Angulata): A Review Article - Daipadli, Daipadli; Shabrina, Ayu; Yuliani, Sapto; Nurkhasanah, Nurkhasanah (Universitas Wahid Hasyim Semarang, 2023)
Litsea angulata, more commonly known as Kalangkala, is a type of plant that belongs to the Lauraceae family. Empirically, the plant has been used traditionally by local people for the treatment of boils, diarrhea, stomachache, dyspepsia, gastroenteritis, diabetes, insect bites, and anti-irritation. This review article aims to find out the results of phytochemical screening of metabolites from parts of Kalangkala plant with various solvents as well as the results of the tests of antioxidant and antibacterial activities that several researchers have carried out. The method used was a literature search on Google Scholar and Pubmed with the keywords kalangkala, Litsea angulata, phytochemical screening, antioxidant, and antibacterial. The results of this review showed that various solvents, such as water, ethanol, methanol, N-hexane, and ethyl acetate in seed, fruit flesh, bark, stem, and leave parts of Kalangakala plant produces different amounts of secondary metabolites. Secondary metabolites such as alkaloids, flavonoids, saponins, and tannins extracted well using etanol as a solvent due to their polarity. The results of the antioxidant activity showed that the part of kalangakala plant such as the bark of the tree, has a very good antioxidant activity of 2.41 ppm when tested using ethyl acetate solvent. Furthermore, the results of the antibacterial activity test show an inhibition of 50 mm on S. mutans bacteria when tested using ethanol solvent. In conclusion, kalangkala plant has secondary metabolites which act as antioxidants and antimicrobials that also potential to developed as traditional medicine.